2008
DOI: 10.1002/cncr.23341
|View full text |Cite
|
Sign up to set email alerts
|

Wilms tumor gene protein 1 is associated with ovarian cancer metastasis and modulates cell invasion

Abstract: The data from the current study identify a novel regulatory mechanism for the control of WT1 expression and provide evidence for a functional role of WT1 protein in the control of cellular invasive activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 52 publications
(76 reference statements)
1
28
0
Order By: Relevance
“…P53, SP17, NY-ESO-1, survivin, and WT1 are immunogenic target antigens in EOC. Rates of observed (over)expression of p53, SP17, survivin, and WT1 in 48.0%, 68.9%, 90.0%, and 56.3% of EOC patients, respectively, are in agreement with previous studies [16, 24, 40, 41]. NY-ESO-1 expression was seen in 11.0% of tumors in our cohort which is in agreement with the results of others [42, 43].…”
Section: Discussionsupporting
confidence: 93%
“…P53, SP17, NY-ESO-1, survivin, and WT1 are immunogenic target antigens in EOC. Rates of observed (over)expression of p53, SP17, survivin, and WT1 in 48.0%, 68.9%, 90.0%, and 56.3% of EOC patients, respectively, are in agreement with previous studies [16, 24, 40, 41]. NY-ESO-1 expression was seen in 11.0% of tumors in our cohort which is in agreement with the results of others [42, 43].…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies have shown that three-dimensional collagen I (3DCI) gels, a microenvironmental component relevant to that encountered by metastasizing ovarian carcinoma cells 11, 12, dramatically modulates cell behavior and promotes a pro-invasive phenotype 6, 7, 13-16. Specifically, our data demonstrate that 3DCI enhances the ability of cells to migrate through upregulation of membrane Wilms’ tumor gene product 1 17 and actinin alpha-4 13, and to digest extracellular matrix via upregulation of membrane type-1 matrix metalloproteinase 6, 7, 15. These findings led to the speculation that other cellular mechanisms pertinent to pro-invasive and migratory behavior, such as cell-matrix adhesion, may be altered through interaction of cells with 3DCI as well.…”
Section: Introductionmentioning
confidence: 60%
“…This procedure was performed as previously described [40-42]. Antibodies were used at the following dilutions: 1:100 mouse anti-human-versican (clone 12C5) in 3% BSA in a solution of 50 mM tris-buffered saline, pH 7.4, 150 mM NaCl, and 0.05% Tween-20 (TBST) (Sigma; St. Louis, MO) and 1:200 mouse anti-human-β-tubulin in 3% BSA in TBST.…”
Section: Methodsmentioning
confidence: 99%